Match demands of female team sports: a scoping review - Armendáriz, M. L. P.; Spyrou, K.; Alcaraz, P. E. (Biology of Sport, 2024)
This scoping review aimed to characterize and quantify the external load demands of professional female team sports, in terms of total distance [TD], moderate-speed [MSR] and high-speed running [HSR], sprint, accelerations [ACC], and decelerations [DEC]. A search was conducted in PubMed, Scopus, and Web of Science until 15/04/2023. The Risk of Bias Assessment Tool for Nonrandomized Studies (RoBANS) was used. Eighty-six articles were eligible for inclusion in this review, with 40 in soccer, 23 in rugby (6 rugby union, 3 rugby league, and 14 rugby sevens), 8 in field hockey, 8 in basketball, 6 in handball, and 1 in futsal. Soccer is the most investigated sport, and players perform ~9500 m TD, of which ~580 m is performed in HSR, and with a great number of ACC, DEC, and sprints. Rugby league and union players cover a greater distance (~5450 m) when compared to rugby sevens (~1550 m); however, rugby sevens is more demanding in terms of high-intensity actions. Field hockey players perform ~5400 m TD with high-intensity and sprint actions. Women`s indoor sports are less studied, and basketball players cover ~5300 m TD, of which 7% is performed in MSR. Handball players perform ~3500 m TD and cover ~423 m in MSR and ~141 m in HSR, and futsal players perform ~5 m × min-1 in HSR and they do a great number of high-intensity activities (HSR, ACC, and DEC). Considering the high physical demands experienced by female athletes, professionals could use the present results for training and return to competition schedules.